Pengaruh Bimbingan Kelompok Teknik Experiential Learning Terhadap Peningkatan Self-Efficacy Siswa Di Sman 1 Gebog - Muhammad Irsyad Syaifuddin (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
The purpose of this study was to determine the implementation of group guidance services with the experiential learning method in increasing self-efficacy in students of SMA Negeri 1 Gebog. The approach to this study was a one-group pretest-posttest design. The results of the study showed an increase in self-efficacy based on the results of the pretest data, the average level of self-efficacy before participating in group guidance with the experiential learning method with a score of 55.5. After participating in group guidance with the experiential learning method, the average value of the posttest was obtained, namely83,875. This shows that there is an increase in self-efficacy in students of 28,375. Resultsquasiobtained the probability figure Asymp. Sig. (2-tailed) of the level of student self-efficacy of 0.012 or probability below alpha 0.05 (0.012 < 0.05). From these results, H0 is rejected and H1 is accepted so it is concluded that the implementation of group guidance services with experiential Learning techniques can improve student self-efficacy. Keywords: Self Efficacy, Group Guidance, Experiential Learning Techniques